EXPERIMENTAL DETERMINATION OF THE POWDER QUANTITY IN THE IGNITION CARTRIDGE FOR THE REUSABLE TRAINING-PRACTICE MORTAR ROUND FOR FIRING ON SHORT DISTANCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article presents an experimental investigation for the powder quantity in the ignition cartridge for the reusable training-practice mortar round for firing on short distances, which is part of a training simulator for mortar crews. A formula for approximately calculating of the required amount of quantity of the gun powder in the ignition cartridge for many times used training-practice mine  for shooting at a distance of 100 meters is presented in the article.  The experimental investigation and the statistical hypothesis checking confirm that the formula can be used for  practically determination of  the required amount of charge in the ignition cartridge.